(untitled) (PERcursos Linguísticos, 2020)
Abstract: As presented in the studies by Cummings (2017), Volden (2017), Loukusa (2017), Stemmer (2017), among other researchers, the approximation of health sciences with studies of pragmatics the characterization and management of an extensive group of language disorders, which cause deficits in human interpretation and communication. Pragmatic deficiencies include autism spectrum disorder, intellectual deficits, dementia, and damage to the right hemisphere. The objective in this work is, therefore, to present the general aspects that guide a pragmatic clinical aspect (Cummings, 2017), from cases that involve the study and clinical management of pragmatic disorders (Brinton, Fujiki, 1994; Abusamra et al, 2009; Loukusa, 2007, 2017), for a brief analysis of conversations and other forms of discourse in this perspective. Finally, we also seek to elucidate pragmatics as a transdisciplinary science and the benefits of this scope for the scientific impact of the area. Keywords: Clinical pragmatics. Cognitive pragmatics. Theory of mind. Language Pathologies.